Peran Program Tahfidz Camp dalam Pembinaan Hafalan Al-Qur’an pada Siswa Sekolah Dasar: Studi di SD Muhammadiyah Medan 08 (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
The teaching of the Qur’an in formal educational institutions has increasingly developed through various innovative programs, one of which is the Tahfidz Camp program. This program is designed to provide a more intensive learning experience in memorizing the Qur’an for students. This study aims to analyze the role of the Tahfidz Camp program in fostering Qur’anic memorization among elementary school students at SD Muhammadiyah Medan 08. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation during the internship activities. The results indicate that the Tahfidz Camp program significantly contributes to improving students’ memorization of the Qur’an, both in terms of the quantity of memorization and the quality of recitation. In addition, the program enhances students’ motivation to learn, discipline, and religious character formation. A supportive learning environment and intensive learning methods are key factors in the success of this program. Therefore, Tahfidz Camp can serve as an effective strategy in fostering Qur’anic memorization at the elementary school level.